Sr, Fe Co-doped Perovskite Oxides With High Performance for Oxygen Evolution Reaction - Guo, Qiang; Li, Xiang; Wei, Haifei; Liu, Yi; Li, Lanlan; Yang, Xiaojing; Zhang, Xinghua; Liu, Hui; Lu, Zunming (Frontiers in Chemistry, 2019)
Developing efficient and earth-abundant electrocatalysts for the oxygen evolution reaction (OER) is still a big challenge. Here, perovskite La0.4Sr0.6Ni0.5Fe0.5O3 nanoparticles were rationally designed and synthesized by the sol-gel method with an average size around 25 nm, and it has a remarkable intrinsically activity and stability in 1M KOH solution. Compared with other perovskite (LaNiO3, LaFeO3 and LaNi0.5Fe0.5O3) catalysts, La0.4Sr0.6Ni0.5Fe0.5O3 exhibits superior OER performance, smaller tafel slope and lower overpotential. The high electrochemical performance of La0.4Sr0.6Ni0.5Fe0.5O3 is attributed to its optimized eg filling (~1.2), as well as the excellent conductivity. This study demonstrates co-doping process is an effective way for increasing the intrinsic catalytic activity of the perovskite.